Protective effects of trehalose on ruminant sperm characteristics: A meta-analysis - Pamungkas F. A.; Sholikin Banti M.M.; Priyatno T. P.; Herdis; Kostaman T.; Santoso; Kusumaningrum D. A.; Hayanti S. Y. (BIO Web of Conferences)
Sperm cryopreservation adds to the extension of reproductive techniques. The composition of the semen diluent's extender, such as trehalose, is one of the most fundamental factors affecting cryopreservation. The objective of the research is to find out the cryoprotectant impacts of various concentrations of trehalose because of the post-thaw quality of ruminant spermatozoa. The data was based on scientific articles that were distributed via Web engines. The following stage was the assessment of reasonableness concerning the exploration subject and study goals, after which 22 papers were chosen for the data set. To retrieve statistically investigated data from the literature, a mixed model was used. A fixed effect was used to analyze the varying degrees of fixation of trehalose in the semen diluent on ruminant sperm quality. The findings indicated that increasing the trehalose content in the semen diluent increased the motility percentage and the hypoosmotic swelling test while decreasing the abnormalities. The recommended optimal level of trehalose addition to maximize sperm motility is around 98.2 mM, or to optimize the hypoosmotic swelling test value, it is about 74 mM. Trehalose improves the quality of ruminant spermatozoa after being frozen and thawed, so it is recommended that trehalose be used to protect spermatozoa during the cryopreservation process.